(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
This research includes an introduction to organic chemistry in the human body, compounds, their importance, composition, types and presence , the functional group is a group of atoms linked by strong covalent bonds and tending to function in chemical reactions as a single unit. You can think of functional groups as tightly knit “cliques” whose members are unlikely to be parted. Five functional groups are important in human physiology; these are the hydroxyl, carboxyl, amino, methyl and phosphate groups